2017
DOI: 10.1038/s41598-017-16545-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profile analysis reveals the regulation mechanism of floral sex differentiation in Jatropha curcas L

Abstract: The seeds of Jatropha curcas contain a high percentage of biodiesel. However, low seed yield which was limited by its poor female flowers was a bottleneck for its utilization. Here, we compared the transcriptomic profiles of five different samples during floral sex differentiation stages using Illumina Hiseq 4000. Our results showed that hundreds of differentially expressed genes (DEGs) were detected in floral sex initiation period, but thousands of DEGs were involved in the stamens and ovules development proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…In a previous study, the lower fruit yield was limited by poor female flowers in J. curcas, and the female floral differentiation could be initiated by inhibiting the expression of TS2, a gene for carpel abortion in J. curcas [26]. Additionally, our previous study also found that the DEGs were mainly down-regulated in the female floral differentiation process [27]. Thus, we suggested that some genes might inhibit the female floral differentiation, which resulted in the lower fruit yield in J. curcas.…”
Section: Differential Expressed Gene Analysismentioning
confidence: 85%
“…In a previous study, the lower fruit yield was limited by poor female flowers in J. curcas, and the female floral differentiation could be initiated by inhibiting the expression of TS2, a gene for carpel abortion in J. curcas [26]. Additionally, our previous study also found that the DEGs were mainly down-regulated in the female floral differentiation process [27]. Thus, we suggested that some genes might inhibit the female floral differentiation, which resulted in the lower fruit yield in J. curcas.…”
Section: Differential Expressed Gene Analysismentioning
confidence: 85%
“…Despite the expression of all JcRbohs, the transcript of JcRbohH was only detected in late stages of ovule and stamen development as well as a mixed sample of root, mature leaf, flower, developing seed, and embryo (Natarajan & Parani, 2011;Hui et al, 2017), and the transcript level was shown to be extremely low. Manuscript to be reviewed PID2 for JcRbohB, JcRbohC, and JcRbohD, respectively.…”
Section: Expression Profiles Of Jcrboh Genesmentioning
confidence: 97%
“…ZaUBQ was selected as an internal control according to a previous study [2]. The 2 -ΔΔCt method was used to calculate the relative expression levels of the genes in different samples [63]. Fr1 (Fruit 1) was used as a control sample to estimate the relative expression of the DEGs associated with terpenoid compounds and fatty acid metabolism during the fruit development and maturation process in this study.…”
Section: Quantitative Real-time Pcr Analysismentioning
confidence: 99%